STUDI TENTANG SONGKOK RESAM PADA MASYARAKAT BANGKA BELITUNG - Indah Pratiwi, Dra. Zubaidah, M.Sn., Dra. Zubaidah, M.Pd. (Universitas Negeri Padang, 2017)
Bangka Belitung community, 2) materials and tools used in the process of making songkok resam, 3) to know anyone who use the songkok resam at traditional ceremony of Bangka Belitung, 4) Knowing the function and meaning of songkok Resam on customs clothing Bangka Belitung. The data sources of this research is primary data source and secondary data source. Primary data source is data collected directly from result of observation to informant through interview process. While the secondary data comes from data obtained through documentation study, personal documentation and reference books and internet. The research found that is songkok resam is one of Bangka typical craft made from resam material. Materials and tools used to make the songkok resam namely: resam, bubut, honey candle, needle, mold, getah samek. The function of songkok resam is as the head cover for men when performing worship, attending parties, traditional events, religious events and so forth. The meaning of songkok resam is as a symbol of Bangka community identity and customs / customs of Bangka community.